Water quality of springs in Badigad Catchment, Western Nepal - Bhusal, Jivan; Gyawali, Prakash (Bulletin of the Department of Geology, 2017)
Population growth and intense agricultural activities in Nepal has caused substantial increase in demand for fresh water. As there is limited access to surface water in most parts of the country, groundwater and springs are the principal water sources for irrigation and drinking purposes in the Terai and hilly region, respectively. The present study carries out the water quality analysis of 30 spring samples in the Badigad Catchment from Gulmi and Baglung Districts. The study was made to analyse suitability of spring waters of the Badigad Catchment for irrigation and drinking purposes. The physiochemical parameters were analysed using standard methods in the site and laboratory. Average value for pH of the sample was 7.8 with conductivity value ranging from 630 to 1500 micro Siemens/cm. The bicarbonate alkalinity ranges from 140 to 350 mg/L, indicating a medium salinity hazard in the catchment. The water in the catchment was found to be moderately hard with an average of 75mg/L CaCO3 hardness. Nitrate, sulphate, ammonia, chloride, fluoride and sodium absorption ratio were found to be